Schizophrenia in Chinese and U.S. Online News Media: Exploring Cultural Influence on the Mediated Portrayal of Schizophrenia. Issue 5 (4th May 2018) - Yang, Yiyi; Parrott, Scott
ABSTRACT: Drawing on the constructionist framing approach, this quantitative content analysis compares online news coverage of schizophrenia in China and the United States in 2015. Incorporating the concept of individualism–collectivism, this study seeks to unveil the effects of culture on the framing of causes, solutions, responsibility attribution, and discourse types. The findings reveal that the link between cultural orientation and the media's framing of schizophrenia is not simple, as both cross-cultural consistency and differences were observed. In addition, compared to U.S. online media, Chinese online news outlets were more likely to cover schizophrenia episodically, while placing more problem-solving responsibility on society. Moreover, examining stigma and challenge cues, this study also found that schizophrenia was more severely stigmatized in Chinese than in U.S. online news platforms. Theoretical and practical implications are discussed.